Tingkat Pemahaman Literasi Mitigasi Bencana Siswa Pada Pembelajaran Geografi Dalam Kurikulum Merdeka di Sman 07 Kota Bengkulu - Anita, Yeni; Supriyono; Zairin (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2025)
Indonesia is a country with a high risk of natural disasters, so disaster mitigation literacy needs to be instilled from an early age through formal education in schools. This study aims to determine the level of understanding of disaster mitigation literacy among students in Geography learning using the Independent Curriculum at SMAN 7, Bengkulu City. This study used a quantitative descriptive approach, with data collection through questionnaires distributed to 104 randomly selected eleventh-grade students. The data obtained were analyzed using descriptive statistics to determine the percentage of student\ understanding. The results showed that the majority of students had an understanding level ranging from understanding to very understanding, with an average percentage above 76 percent. These findings indicate that integrating disaster mitigation material into Geography learning can improve students' disaster literacy. This study concluded that strengthening contextual and practical learning methods, such as local case studies and disaster simulations, is very important for students to be better prepared to face disaster risks in vulnerable areas. The results of this study are expected to be a reference for teachers, schools, and policymakers in developing Geography learning strategies that aremore applicable and relevant to local conditions.